Challenges of nurses and caregivers in the care of children in oncological treatment (Revista Contexto & Saúde, 2025)
The practice of caring in pediatric oncology is challenging, since it requires, in addition to specific material and therapeutic resources, a health team and caregivers attentive to the demands inherent to this universe. Thus, the objective was to analyze the challenges of caring for children with cancer from the perspective of nurses and caregivers. It is a strategic social research, with qualitative approach, which had as participants 18 nurses and caregivers of children in oncological treatment of two public health institutions of the hinterland of Pernambuco. Data collection was carried out by semi-structured interviews, analyzed in the light of the Complexity Paradigm. Thus, from the reports of the research participants, several challenges were identified as a result of cancer treatment emerged as a challenge for nurses and caregivers in the follow-up of the affected child, what required these actors the development of mechanisms to deal with situations of uncertainty and insecurity, in order to provide care without being overwhelmed by the difficulties imposed by the context of the disease. Nurses and caregivers listed relevant aspects about barriers to cancer therapy, revealing strategies used to overcome barriers found and, thus, it was shown that the emotional of the interviewees appeared as a hindrance to treatment, beyond the recognition of the existence of gaps in the training of nurses, limiting their performance. It is concluded, therefore, that the challenges experienced in the care of children with cancer involves a context of significant changes in the routine of the family and the child, as well as difficulties in the logistics of displacement and hospitalization, and the awakening of fears and uncertainties before the treatment brings negative impacts on the experience of this disease process.
Keywords: Child health; Nursing care; Oncological nursing; Neoplasms; Caregivers